Experimental and CFD analysis of solar air heater duct roughened with multiple broken transverse ribs: A comparative study. (August 2019) - Singh, Inderjeet; Vardhan, Sachit; Singh, Sukhmeet; Singh, Amritpal
Highlights: Two novel ribs are investigated and compared for performance enhancement in SAH's. Both experimental and CFD analysis has been carried out. The effect of various roughness and flow parameters has been presented. Flow visualization for thermal characteristics and air-flow phenomena. Abstract: Lower thermal performance of conventional solar air heaters (SAH) can be enhanced by implementing small sized roughness elements on the air-flow side of the absorber plate. This article presents the results of a comparative study of two novel ribs arrangement namely multiple broken transverse ribs and square wave shaped ribs for performance enhancement in SAH's. The investigation incorporates rib parameters as P/e = 10, e/D = 0.043 and W/w = 7 for both arrangements and investigated at six levels of Reynolds number ranging 3000–18, 000. The effect of two different multiple shaped ribs on heat transfer and friction factor characteristics has been investigated using experimental and numerical investigation. The optimum parameters based on thermo-hydraulic performance has been evaluated. The CFD methodology has been validated for the smooth and roughened duct. Maximum thermal enhancement of 2.50 times with corresponding pumping power penalty of 3.92 times is obtained for square wave shaped ribs whereas in case of multiple broken ribs, the enhancements are 3.24 and 3.85 times respectively. The experimental results are illustrated and justified with the visualization of flow pattern and contours of temperature, pressure and turbulence.